First records of two Cuthona species (Gastropoda: Nudibranchia) in the Adriatic Sea - Lovrenc Lipej; Borut Mavrič; Domen Trkov (Natura Sloveniae)
Authors are reporting on the first records of two nudibranch species of the genus Cuthona in the Slovenian part of the Adriatic Sea. In the period from September 2014 to March 2015, specimens of Cuthona genovae and C. miniostriata were found at different localities in the mediolittoral and upper infralittoral belts. The findings of both Cuthona species represent the first records in the Adriatic Sea.